Numeracy Literacy Module Based on Local Culture: Effort to Improve Numeracy Literacy Skill - Rahmadeni, Fevi; Septiana, Anisya; Syaripah, Syaripah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Numeracy literacy, is one of the skills that must be possessed by the younger generation in facing the 21st century and required in the world of work nowadays. This ability allows a person to analyze the information presented in various forms of data presentation, and make the right decisions on the available information. In addition, the world of work in the current era of 4.0 also requires workers who have numeracy literacy skills. The purpose of this research is to develop a numeracy literacy module that meets the criteria of being valid, practical, and effective for use as learning resource of numeracy literacy for students. This type of research is research and development and uses the Plomp development model which goes through 5 stages, namely the preliminary investigation phase, the design phase, the realization or construction phase, the testing, evaluation, and revision phase, and the implementation phase. As for this research, it did not reach the implementation phase considering the limited time of the study. The results showed that the developed module had met the valid criteria with a score of 3.7, practical with a score of 3.7, and effective with a student completeness score of 83.3%.